Enlargement of Tubers from Flower Blooming to Seeds Ripening in Konjac Plant (Amorphophallus muelleri Blume) - Lakitan, Benyamin; Nurshanti, Dora Fatma; Muda, Strayker Ali; Yakup, Yakup; Jaafar, Nardiah Rizwana; Illyas, Rosli Md. (AGRIVITA Journal of Agricultural Science, 2025)
The cultivation of konjac plants (Amorphophallus muelleri Blume) is mainly initiated by the accumulation of glucomannan in their tuber. Many studies of konjac plants are limited until konjac tubers are suitable for harvest, not extended to the flowering stage. This study focused on tubers' development in the flower bud formation phase until seed development. The results of this study show that only one flower grows from each tuber. It takes 40+2 days for the konjac flower to bloom fully but 3+1 days for the flower to wither. The weight, diameter, and thickness of the konjac tubers used as planting material were 0.342+0.014 kg, 8.23+0.26 cm, and 5.75+0.17 cm, respectively, and significantly grew to 2.70+0.156 kg, 19.96+0.560 cm, and 12.73+0.335 cm, respectively at the time of harvest. Konjac plants promote thick lateral roots at the base of the petiole and fibrous roots on the tuber skin. During the enlargement of the tubers, the thickness and diameter ratio did not change. The cross-sectional shape of petioles and spadix is slightly oval. The number of seeds per plant correlated with the female flower's length, diameter, and cylindrical area. Finally, tubers decompose, and a new one or more starts to grow.